Analisis Peningkatkan Pendapatan Fee Based Income dengan Penggunaan Aplikasi Mobile Studi Kasus Pada KSPPS BMT UGT Nusantara - Saiful Bakhri; Muchamad Iqbal Fatah; Fatmah Hanum (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2021)
Cooperatives have the opportunity to empower their members who have businesses such as basic food traders, street vendors, and other tradesmen, to be able to offer PPOB payment services owned by cooperatives. The type of research used in this study is a qualitative method. From the results of research that has been done, there are factors that influence members in using the UGT Mobile application because it is easier to use than mobile banking in a number of banks, safer because it is easy to communicate and handle complaints, feel ownership because as a member is also the owner of a cooperative. BMT UGT members are less than optimal in using the UGT Mobile application due to lack of knowledge about the UGT Mobile application. The increase in fee-based income for BMT UGT is less than optimal due to the lack of maximum socialization of Mobile UGT to members of BMT UGT and the lack of equal distribution of employee knowledge in terms of the benefits of the Mobile UGT application